Value-Added Biogas Production and Its Effect on Ethiopia's Rural Energy Security - Gemechu Kaba SORI (Indonesia Strategic Sustainability, 2023)
Ethiopia has access to a variety of renewable energy sources. A renewable energy source made from agricultural waste, forest products, and other biological resources is bioenergy. There are few studies demonstrating the added value of bioenergy production and its importance in Ethiopia's energy security. Therefore, the purpose of this study is to evaluate the gross value added in the production of bioenergy and how it affects energy security. Primary and secondary data from various sources were used and descriptively examined. According to the findings, the gross value added at all levels of the value chain for the generation of biogas from installed biodigesters was estimated to be ETB 175.619 million (USD 6.23 million), or roughly 0.0074 percent of the nation's GDP in 2018. Currently, only a few regions of the country use the household-level biogas that provides benefits to 180,000 rural residents. In Ethiopia, there are approximately 1.1 million homes that might adopt dung-based bio-digesters. It is crucial to use this biogas feedstock for cooking, but it would also be crucial to provide the grid with the energy. By doing this, the sector's contribution to the GDP of the nation and the gross value added from the production of biogas would both significantly grow. Therefore, significant assistance for biogas-based power generation is required within the framework of sectoral policies at the federal level.